Use of natalizumab in multiple sclerosis: current perspectives. (1st September 2016) - Gandhi, Sirin; Jakimovski, Dejan; Ahmed, Rahil; Hojnacki, David; Kolb, Channa; Weinstock-Guttman, Bianca; Zivadinov, Robert
ABSTRACT: Introduction : Natalizumab is an efficacious monoclonal antibody approved for use in relapsing-remitting multiple sclerosis (RRMS). Multiple studies have demonstrated reduced relapse rate, decreased disability progression and prolonged disease-free intervals with natalizumab use. However, natalizumab is associated with an increased risk of progressive multifocal leukoencephalopathy (PML), thus restricting its widespread use with populations at high risk for developing PML. Recently, the effect of natalizumab in secondary-progressive (SPMS) population has been explored. Areas covered : This review highlights the pathophysiology behind disease progression in MS and summarizes various attributes of natalizumab including: its pharmacological properties and global economic impact, results of clinical efficacy studies, its role in SPMS, pregnancy and its adverse events profile including PML and discontinuation protocols. Expert opinion : Despite an established role in reducing RRMS disease activity, natalizumab has found limited use in SPMS due to insufficient evidence of efficacy. Current disease-modifying therapies exert modest overall benefit in SPMS owing to its complex pathophysiology, higher prevalence of comorbidities and increased PML risk with age and lack of reliable outcome measures. Finding more appropriate MRI and clinical outcome measures is quintessential for designing future randomized trials and possibly exploring primary neuroprotective agents for treating SPMS.